AB0262 PTPN22 1858C>T polymorphism is a negative biomarker of (eular good) response to methotrexate in a cohort of early rheumatoid arthritis. (23rd January 2014) - Fedele, A.L.; Tolusso, B.; Totaro, M.C.; Bosello, S.L.; Canestri, S.; Gremese, E.; Ferraccioli, G.
Abstract : Background: A tight control strategy is necessary for an optimal management of early rheumatoid arthritis (ERA). However, it is not sufficient because there is a huge need of biomarkers in order to predict drug responsiveness and improve assessment of both disease activity and structural damage. Objectives: To identify possible biomarkers predictors of response to Methotrexate (MTX) treatment in a cohort of ERA treated according to a tight control protocol. Methods: A total of 286 consecutive patients with ERA were enrolled in the study. All patients were treated with MTX for three months, then with a combination with Tumor Necrosis Factor (TNF) blockers if they had an incomplete response after 3-month treatment period. At baseline and every 3 months demographic and immunological data and the ACR/EULAR core data set [erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), swollen joint count (SJC), tender joint count (TJC), physician and patient global assessment, pain, health assessment questionnaire (HAQ)] were recorded. Moreover, DNA from all patients was genotyped for the PTPN22 1858C>T by polymerase chain restriction fragment length polymorphism method. The EULAR response criteria were used as the primary outcome measure at 3- and 6-month follow-up visits. The likelihoods of achieving a good EULAR response (defined as a disease activity score (DAS) <2.4 and a fall in this score from baseline by >1.2) at the third month and a sustained remission at the sixth month follow-up visits (defined as a DAS value of <1.6 for at least two consecutive visits 3 months apart) were evaluated using univariate and multivariate logistic regression and the results were expressed as ORs with 95% CI. Results: 45.7% of the patients reached a good EULAR response at the third month and 21.8% reached a sustained remission at the sixth month of follow-up. A lower percentage of ERA patients carrying the PTPN22 1858 CT/TT genotype reached a good EULAR response to MTX treatment after 3 month follow-up (22.6%) and a sustained remission at the sixth month of follow-up (6.7%) compared to subjects with the CC genotype (good EULAR response at the third month: 49.1% (OR 0.30, 95%CI 0.13-0.73); sustained remission at the sixth month 24.1% (OR 0.23, 95%CI 0.05-0.98)). The influence of each baseline parameter (demographic, genetic and immunological) on the likelihood of reaching a good EULAR response was evaluated and the PTPN22 CT/TT genotype arose as a significant predictor of good response to MTX at the third month (OR 0.30, 95%CI 0.13-0.75). When considering the sustained remission at the sixth month, the PTPN22 CT/TT genotype again proved as a "negative" predictor of this target (OR 0.19, 95%CI 0.04-0.86), together with female sex (OR 0.47, 95%CI 0.23-0.96) and "having at onset an ESR>30 mm/h" (OR 0.28, 95%CI 0.14-0.55). Conclusions: The PTPN22 CT/TT genotype predicts a worse response to MTX therapy at the third month of follow-up and a lower likelihood of reaching sustained remission at the sixth month, together with female sex and higher ESR levels at baseline. Disclosure of Interest: None Declared